Seven faces of womens sport - Reid, Irene A.; Dennehy, Jane (Emerald Publishing Limited, 2018)
Media and political figures often assert that progress towards achieving gender parity has advanced. However, circumstances around recent major sports events such as the Women's Football World Cup and Olympic Games suggest otherwise. From controversy around facilities to miniscule commercial sponsorship, from body confidence to physical literacy, from grassroots to elite performance these events reveal ideologies and barriers that mitigate against parity for women's sport remaining entrenched. An informed critical examination of interconnected issues around women and sport in the twenty-first century is absent from current scholarship. This book will explore some of the intersecting issues through the lens of 7 faces: governance, economics, nationhood, competition, bodies, sport for development and media. The collection seeks to amplify the ways in which inequalities are sustained by struggles between dominant social, political and economic power networks. We argue that only by making visible this complex matrix, does it become possible to create agendas for more rapid change to rebalance existing gender inequalities. The book seeks to disentangle some of the issues, and to disrupt conventional ways of thinking about gender inequalities in sport. Our thesis is that change is slow, but investment in different skills and knowledge could direct sustainable and strategically relevant change for women's sport.